Mechanisms of Urge: How Flow Experience and Time Pressure Shape Consumer Behaviour in Live Shopping - Jaolis, Ferry; Wijaya, Serli; Pingkan, Jessica (Organizations and Markets in Emerging Economies, 2026)
Grounded in the Stimulus-Organism-Response model and contextualized in the live shopping realm, this study investigates how host credibility and social presence (S) affect consumers’ flow experience (O) and their urge to buy impulsively (R). It also explores the moderating effect of time availability on the organism-response association. The authors used SmartPLS 4.0.9.6 to analyse the 244 valid responses from Indonesian Shopee Live consumers. The results empirically demonstrate that while both host credibility and social presence had positive significant impacts on consumers’ flow experience, they cannot directly affect their urge to buy impulsively without the formation of flow experience. The results also revealed that Indonesian consumers’ impulsive buying was not always behavioural, but also situational, justifying the moderating effect of time availability. The findings of this study suggest that a pleasant and entertaining experience facilitates impulsive buying in live shopping, led by credible hosts and real-time social interactions.
Keywords: host credibility; social presence; flow experience; urge to buy impulsively; time pressure